2016
DOI: 10.5430/ijba.v7n6p22
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effect of the Organization’s Internal Control System on Organizational Effectiveness: A Jordanian Empirical Study

Abstract: This study aims to investigate the impact of the internal control system (Control environment, Communication, Risk management, Control activities and Monitoring) on organizational effectiveness in Jordan. The organizational effectiveness was studied through three approaches namely; organizational ability to achieve its goals (Goal approach), organizational ability to control and maintain the needed resources (Resource Control approach) and the (Multiple Constituency approach) which deals with organizational co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 51 publications
5
53
1
9
Order By: Relevance
“…The statistical significance of hypotheses 1 confirms the Advances in Social Science, Education and Humanities Research, volume 377 implementation of internal control improves organizational performance. This research similar with [2]; [6]; [11]; [12] that showed the higher the internal control system applicability, the higher the applicability of organization effectiveness. Internal controls help the financial sector in presenting it's a strong and stable outlook.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The statistical significance of hypotheses 1 confirms the Advances in Social Science, Education and Humanities Research, volume 377 implementation of internal control improves organizational performance. This research similar with [2]; [6]; [11]; [12] that showed the higher the internal control system applicability, the higher the applicability of organization effectiveness. Internal controls help the financial sector in presenting it's a strong and stable outlook.…”
Section: Resultssupporting
confidence: 90%
“…There is a lot of literature that examines the relationship between internal control and organizational performance in various countries as well as industries (for example, [2]; [11]; [12]; [6]. They founded internal control have a significant effect on organizational performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational performance measurement has become an increasingly important matter in order for organizations to survive under the pressure of world class competition (Skrinjar et al, 2008;Al-Syaidh et al, 2015;Mahadeen et al, 2016). Financial performance refers to "a measure of the change of the financial state of an organization, or the financial outcomes that results from management decisions and the execution of those decisions by members of the organization" (Carton, 2004).…”
Section: Financial Performancementioning
confidence: 99%
“…However, several definitions of organizational commitment have surfaced from various quotas. From the varied definitions, organizational commitment can be coined to mean the link between an individual and an organization, as well as the beliefs in the goals of the organization thus making tremendous efforts to reach the goals of the organization by being a part and parcel of it (Amari, 2012;Mahadeen et a., 2016). Allen and Mayor (1990) conducted a study which has dominated the academic field of organizational commitment.…”
Section: Organizational Commitmentmentioning
confidence: 99%